2022
DOI: 10.1530/raf-21-0100
|View full text |Cite
|
Sign up to set email alerts
|

Preantral follicle population and distribution in the horse ovary

Abstract: Characterization of the ovarian preantral follicle population is a necessary step to improve understanding of folliculogenesis and ovarian physiology. Therefore, in the present study, the preantral follicle population in the equine ovary in young and old mares was investigated according to follicular morphology, follicular class, distance from the geometric center using ovarian maps, and follicular density within ovarian portions (lateral vs. intermediary) and regions (dorsal vs. ventral). Ovaries were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Interestingly, the aforementioned studies reported that follicular clustering increases with age in both species, perhaps due to expected decreases in follicle density and regular follicular activity over time [ 31 ]. However, in the present study, it was found that clustering decreased with age, a finding that is supported by the fact that in old mares, the spatial distribution of follicles exhibits a more dispersive pattern [ 18 , 19 ]. The working hypothesis of ovarian plasticity, in which preantral follicles are suggested to migrate throughout the ovarian cortex, postulates that the rigidity of ovarian tissue is a key component of this migration [ 17 ].…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Interestingly, the aforementioned studies reported that follicular clustering increases with age in both species, perhaps due to expected decreases in follicle density and regular follicular activity over time [ 31 ]. However, in the present study, it was found that clustering decreased with age, a finding that is supported by the fact that in old mares, the spatial distribution of follicles exhibits a more dispersive pattern [ 18 , 19 ]. The working hypothesis of ovarian plasticity, in which preantral follicles are suggested to migrate throughout the ovarian cortex, postulates that the rigidity of ovarian tissue is a key component of this migration [ 17 ].…”
Section: Discussionsupporting
confidence: 78%
“…The working hypothesis of ovarian plasticity, in which preantral follicles are suggested to migrate throughout the ovarian cortex, postulates that the rigidity of ovarian tissue is a key component of this migration [ 17 ]. It has been proposed that primordial follicles may migrate from the more rigid outer regions of the ovarian cortex to the softer, less rigid regions of the cortex, closer to the ovarian geometric center, as they initiate and continue development to the primary stage [ 17 19 , 30 ]. However, it has been shown in the ovaries of women that levels of substances that contribute to rigidity and elasticity of the ovarian extracellular matrix (i.e., collagen, elastin, fibrillin) change as aging progresses [ 32 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations